Konflik dan Peluang Sosial Ekonomi Akibat Kurangnya Lahan Parkir Karyawan di Lingkungan PT. Adonia Footwear Indonesia - Luthfiah Nur Fatikha (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study examines the complex socio-economic dynamics resulting from the limited availability of parking space within the premises of PT Adonia Footwear Indonesia. The imbalance between the high number of employee-owned vehicles and the insufficient parking capacity creates challenges that extend beyond spatial limitations, encompassing issues of safety, user behavior, and the adequacy of supporting infrastructure. In the context of a growing workforce and increasing vehicle ownership, the scarcity of parking facilities has become a pressing concern that requires holistic assessment and problem-solving strategies. The research aims to identify not only the conflicts caused by the shortage of employee parking but also the socio-economic opportunities that arise from this condition. A qualitative descriptive method was applied using a case study approach to capture the detailed and contextual realities of the problem. Data were collected through direct observation, semi-structured interviews with employees, company management, and local residents, as well as documentation review. This triangulation of data sources ensured the validity and richness of the findings. The results indicate that the parking shortage has generated friction between employees and residents living near the factory, primarily due to the use of residential areas for overflow parking. Disputes have arisen over blocked access, noise, and security concerns. However, the situation has also fostered new economic activities, particularly the emergence of informal paid parking services managed by local residents, which provide them with additional income. This dual impact highlights the parking issue as both a source of social tension and a driver of community-based microeconomic opportunities. The study concludes that a collaborative approach between the company and surrounding residents offers a viable and sustainable solution. Initiatives such as formal partnerships for managed parking services, infrastructure improvements, and the implementation of employee vehicle management policies could mitigate conflict while enhancing mutual economic benefits.